2007
DOI: 10.1080/02841850701196922
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced magnetic resonance cholangiography with Gd-BOPTA and Gd-EOB-DTPA in healthy subjects

Abstract: This is an electronic version of an article published in: Nils Dahlström, Anders Persson, Nils Albiin, Örjan Smedby and Torkel Brismar, Contrastenhanced magnetic resonance cholangiography with Gd-BOPTA and Gd-EOB-DTPA in healthy subjects, 2007, Acta Radiologica, (48), 4, 362-368. Acta Radiologica is available online at informaworld TM : http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 29 publications
2
55
1
2
Order By: Relevance
“…Recently, heavily T2-weighted MR cholangiography has been proven to be an accurate modality in diagnosis of acute cholecystitis (4,21). Heavily T2-weighted MR cholangiography detects the water content of bile within intra-and extrahepatic biliary ducts and gallbladder in multiple planes without contrast material but, this modality is sensitive to motion artifacts and is not always decisive (13). Despite their validated clinical utilities US, computed tomography, and heavily T2-weighted MR cholangiography cannot provide functional information, however, they can demonstrate changes secondary to inflammation within gallbladder and biliary system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, heavily T2-weighted MR cholangiography has been proven to be an accurate modality in diagnosis of acute cholecystitis (4,21). Heavily T2-weighted MR cholangiography detects the water content of bile within intra-and extrahepatic biliary ducts and gallbladder in multiple planes without contrast material but, this modality is sensitive to motion artifacts and is not always decisive (13). Despite their validated clinical utilities US, computed tomography, and heavily T2-weighted MR cholangiography cannot provide functional information, however, they can demonstrate changes secondary to inflammation within gallbladder and biliary system.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biliary excretion rate (50%) is significantly more than that of Gd-BOPTA (26). Recently, Dahlström et al compared contrast-enhanced MR cholangiography scans obtained with Gd-BOPTA and Gd-EOB-DTPA in 10 healthy volunteers in a prospectively designed protocol for biliary enhancement dynamics and concluded that biliary enhancement begins earlier and persists longer with Gd-EOB-DTPA (13). There is no consensus reached on when to acquire contrast-enhanced MR cholangiography images after injection, because the clinical experience for Gd-BOPTA-enhanced MR cholangiography is limited.…”
Section: Discussionmentioning
confidence: 99%
“…This allows a functional evaluation of the biliary system within 20 minutes after administration of the contrast agent in the patients with normal liver function (5,(17)(18)(19). In recent years, Dahlström et al (20) compared Gd-BOPTA and Gd-EOB-DTPA enhanced MRC images in terms of biliary tract enhancement in 10 healthy volunteers. In that study, it was emphasized that biliary tract enhancement started earlier and lasted longer with Gd-EOB-DTPA (20).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Dahlström et al (20) compared Gd-BOPTA and Gd-EOB-DTPA enhanced MRC images in terms of biliary tract enhancement in 10 healthy volunteers. In that study, it was emphasized that biliary tract enhancement started earlier and lasted longer with Gd-EOB-DTPA (20). The recommended dose of Gd-EOB-DTPA is 0.025 mmol/kg and is also ¼ of Gd-BOPTA (10).…”
Section: Discussionmentioning
confidence: 99%
“…Gd-EOB-DTPA is eliminated by biliary and urinary excretion; in healthy volunteers, the agent was completely eliminated in almost equal amounts in urine (43.1-53.2z) and feces (41.6-51.2z). 2 Gd-EOB-DTPA has been reported as a biliary contrast agent with T1-weighted MR imaging, [3][4][5][6][7]12,13 and its biliary excretion can also be used this way.…”
Section: Discussionmentioning
confidence: 99%